Regional Variations in the Risk and Severity of Ciguatera Caused by Eating Moray Eels - Thomas Y. K. Chan (Toxins, 2017)
Moray eels (Gymnothorax species) from tropical waters have long been known to be high-risk species, and the consumption of particularly the viscera or ungutted eels can result in severe ciguatera (known as Gymnothorax or moray eel poisoning), characterized by prominent neurological features. In this review, the main objective was to describe the risk and severity of ciguatera caused by eating moray eels in different parts of the world. Moray eels can accumulate very high ciguatoxin (CTX) levels in the flesh and particularly the liver. Therefore, even the smaller ones can be toxic and the consumption of an average portion (particularly liver) can result in severe or fatal ciguatera. Moray eels (particularly when ungutted) must never be served in gatherings since they can cause mass poisoning because of their large sizes and high CTX levels. Apart from regulatory measures restricting or excluding access, the public should be repeatedly warned to avoid eating moray eels.